1981
DOI: 10.1016/0040-1951(81)90251-1
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamics of the Baikal rift zone and plate tectonics of Asia

Abstract: Abstract:We have compiled and analyzed earthquake focal solutions for the territory of Mongolia and its surroundings in order to reveal a spatial variability of stress orientation and stress regimes of the crust. According to the stress inversion results, the SHmax is turning from W-E in the eastern Mongolia to SW-NE in the Gobi Altay and the central Mongolia, and then to S-N in the western part of the region. Comparison with data derived from GPS measurements shows that directions of the strain axes revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
9

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(127 citation statements)
references
References 8 publications
1
117
0
9
Order By: Relevance
“…A right lateral N-S trending fault system is found in Sakhalin and Hokkaido; the formation of this shear zone is thought to be associated with cessation of earlier subduction and reorganization of convergence in the late Cretaceous or Paleogene [Kimura et al, 1983]. This shear zone is thought to be the plate boundary between the North American plate (or a separate Okhotsk plate) and the proposed Amurian plate to the south [Zonenshain and Savostin, 1981], the existence of which has been further supported by regional tectonics and earthquake slip vectors [Wei and Seno, 1995] and a recent GPS study [Takahashi et al, 1999].…”
Section: Tectonic Settingmentioning
confidence: 99%
“…A right lateral N-S trending fault system is found in Sakhalin and Hokkaido; the formation of this shear zone is thought to be associated with cessation of earlier subduction and reorganization of convergence in the late Cretaceous or Paleogene [Kimura et al, 1983]. This shear zone is thought to be the plate boundary between the North American plate (or a separate Okhotsk plate) and the proposed Amurian plate to the south [Zonenshain and Savostin, 1981], the existence of which has been further supported by regional tectonics and earthquake slip vectors [Wei and Seno, 1995] and a recent GPS study [Takahashi et al, 1999].…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Alternatively, the Okhotsk (OKH) and Amurian (AMU) microplates are supposed in place of the North American and Eurasian plates in east Asia [Zonenshain and Savostin, 1981;Seno et al, 1996;Apel et al, 2006]. From our solution GPS2007.0, the rotation rate of the Arctic-Siberian part with respect to the main part of the North American plate is statistically insignificant: 0.016 ± 0.011°/Ma; this fact supports the presence of the North American plate in Siberia although the Bering Sea block probably moves with respect to the North American plate [Fournier and Freymueller, 2007].…”
Section: Relative Plate Rotation Vectorsmentioning
confidence: 99%
“…The latter corresponds to the strain concentration zone along the eastern margin of Japan Sea [9]. As for the Tohoku arc, the start of eastward motion of Amur Plate at around 5 Ma [69] might have resulted in a new plate boundary along the strain concentration zone since 0.5 Ma. Moreover, [36] examined the U-Pb age data of Kurobegawa granite in the Hida mountain range and concluded that the granites were emplaced incrementally through the amalgamation of many intrusions since the late Miocene up to the latest intrusion event at 0.8 Ma, and that such magmatic intrusions caused rapid uplift and erosion of the Hida mountain range in the Quaternary.…”
Section: Tectonic Inversion Of Sedimentary Basins and Related Faultsmentioning
confidence: 98%